Cognitive Control Functions in Unipolar Major Depression with and without Co-Morbid Anxiety Disorder - Lyche, Pia; Jonassen, Rune; Stiles, Tore C.; Ulleberg, Pål; Landro, Nils I. (Frontiers in Psychiatry, 2010)
Background: Impaired cognitive control functions have been demonstrated in both major depression (MDD) and anxiety disorder (A), but few studies have systematically examined the impact of MDD with co-morbid A (MDDA), which is the main aim of this study. Method: We compared patients with MDD with (MDDA; n = 24) and without co-morbid A (n = 37) to a group of healthy controls (HC; n = 92) on three subtests from the Cambridge Neuropsychological Test Automated Battery; intra–extra dimensional, stop signal task, and spatial working memory. These tasks correspond to a theoretical model consisting of three separable but interrelated executive control functions: Shifting, Inhibition, and Updating. A simple psychomotor speed measure was also included. Results: After controlling for age, gender, and education level, the results showed that the MDDA group displayed significantly impaired performance on the functions Shifting and Updating compared to HC. There emerged no significant differences between any of the patientgroups and HC regarding Inhibition. The pure MDD group did not display dysfunctions relative to the HC group on the main executive control variables, but displayed slowed psychomotor speed. Contrary to expectation there were no significant differences between the MDDA and the MDD groups. Conclusion: Co-morbid anxiety should be taken into account when studying cognitive control functions in major depression.